Estudo do grau de conhecimento geral dos donos de cães sobre a leishmaniose visceral canina no município de Lençois Paulista-SP-2012 - Gouveia, Jéssica Cristina Melice [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Leishmaniasis is a zoonosis considered a major public health issue. The World Health Organization estimates that 350 million people are exposed to it, with 2 million new infections, by the different forms of it, a year. In Brazil, the Visceral Canine Leishmaniasis (VL) is an important health issue not only because of its high incidence and transmission, but also because of the possibility of becoming life threatening when associated to poor nutrition and concomitant infections. There have been a growing number of urban outbreaks for 20 years. Rising up a discussion about the ways of control that have been used. These control measures have been incapable of both preventing and eliminating the transmission; they’ve also failed preventing new outbreaks. The knowledge about VL together with local population awareness is a key to establish control campaigns, mobilizing the whole community in sanitary campaigns. The present study evaluated the general knowledge of dog owners about VL and got information to help the establishment of a more accurate and better directed health education against VL in the city of Lençóis Paulista in São Paulo. The inquiry was made before the outbreak occurred in 2009 in the city and after it, by the 120 health agents that work for the city. These agents were trained by health experts both from the region and from UNESP in Botucatu/SP. Their training consisted on especially designed booklets developed to guide them during their fieldwork inquiry, helping them to make accurate interviews to guarantee precise information data collection. There were 390 interviews, divided in 5 city districts, as following: downtown (46), Q1 (134), Q2 (60), Q3 (106), Q4 (38), covering the whole 30km2 of urban area, each neighborhood keeping their actual proportion. The data collected was put in a database and was analyzed, with a frequency distribution, absolute and relative, and a percentage ...

A leishmaniose é uma zoonose considerada um grande problema de saúde pública. A Organização Mundial da Saúde estima que 350 milhões de pessoas estejam expostas ao risco com registro aproximado de dois milhões de novos casos das diferentes formas clinicas ao ano. No Brasil, a importância da Leishmaniose Visceral Canina reside não somente na sua alta incidência e ampla distribuição, mas na possibilidade de assumir formas graves e letais quando associada ao quadro de má nutrição e infecções concomitantes. A crescente urbanização da doença ocorrida nos últimos 20 anos coloca em pauta a discussão das estratégias de controle empregadas. As medidas de controle da doença até agora implementadas foram incapazes de eliminar a transmissão e impedir a ocorrência de novas epidemias. Os conhecimentos sobre a circulação da LVC, assim como sua percepção pela população local, são de grande valia para o estabelecimento de campanhas de controle, pois mobiliza a comunidade em ações sanitárias. Busca avaliar comparativamente o conhecimento geral dos donos de cães sobre a LVC e obter informações para auxiliar na elaboração de uma proposta mais precisa e direcionada de educação continuada em saúde, no que se refere à LVC no Município de Lençóis Paulista - SP. Um inquérito foi desenvolvido para ser aplicado por 120 agentes comunitários de saúde, os quais receberam treinamento por uma equipe de profissionais da área e da UNESP de Botucatu - SP. O treinamento teve como base material especial de apoio apostilado desenvolvido de forma direcionada, contendo instruções gerais para orientar os entrevistadores no trabalho de campo, auxiliando-os na correta realização das entrevistas, de maneira a garantir a precisão das informações coletadas. Foram 390 participantes respondentes, distribuídos em cinco regiões do município, sendo: centro (46), Q1 (134), Q2 (60), Q3 (106), Q4 (38), abrangendo todos os 30km2 de área ...
Keywords: Cão - Doenças; Leishmaniose visceral - Prevenção; Saude publica - Administração; Pessoal da area médica - Treinamento; Educação permanente; Kala-azar